From Fish Scale Gelatin to Tyrosinase Inhibitor: A Novel Peptides Screening Approach Application - Hu, Zi-Zi; Sha, Xiao-Mei; Zhang, Lu; Zha, Min-Jun; Tu, Zong-Cai (Frontiers in Nutrition, 2022)
Bioaffinity ultrafiltration combined with LC-Orbitrap-MS/MS was applied for the first time to achieve rapid screening and identification of tyrosinase inhibitory peptides (TYIPs) from grass carp scale gelatin hydrolysates. The binding mode of TYIPs with tyrosinase was investigated by molecular docking technology. The whitening effect of TYIPs was further studied by evaluating the tyrosinase activity and melanin content in mouse B16F10 cells. Four new TYIPs were screened from hydrolysates, among which DLGFLARGF showed the strongest tyrosinase inhibition with an IC50 value of 3.09 mM. Molecular docking showed that hydrogen bonds were the main driving force in the interaction between the peptide DLGFLARGF and tyrosinase. The addition of DLGFLARGF significantly inhibited the tyrosinase activity and melanin production of B16F10 melanoma cells. These results suggest that DLGFLARGF is a promising skin whitening agent for the treatment of potential pigment-related diseases.